Gastrointestinal discomfort during intermittent high-intensity exercise: Effect of carbohydrate-electrolyte beverage - Shi, X.; Horn, M. K.; Osterberg, K. L.; Stofan, J. R.; Zachwieja, J. J.; Horswill, C. A.; Passe, D. H.; Murray, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
This study investigated whether different beverage carbohydrate concentration and osmolality would provoke gastrointestinal (GI) discomfort during intermittent, high-intensity exercise. Thirty-six adult and adolescent athletes were tested on separate days in a double-blind, randomized trial of 6% and 8% carbohydrate-electrolytes (CHO-E) beverages during four 12-min quarters (Q) of circuit training that included intermittent sprints, lateral hops, shuttle runs, and vertical jumps. GI discomfort and fatigue surveys were completed before the first Q and immediately after each Q. All ratings of GI discomfort were modest throughout the study. The cumulative index for GI discomfort, however, was greater for the 8% CHO-E beverage than for the 6% CHO-E beverage at Q3 and Q4 (P < 0.05). Averaging across all 4 quarters, the 8% CHO-E treatment produced significantly higher mean ratings of stomach upset and side ache. In conclusion, higher CHO concentration and osmolality in an ingested beverage provokes stomach upset and side ache.